MANAJEMEN PENGEMBANGAN PROFESIONALISME GURU MAN DI KOTA BANDAR LAMPUNG - Amalliya Nurjannah; Romlah Romlah; Yetri Yetri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the management of teacher professional development at State Islamic Senior High Schools (MAN) in Bandar Lampung City, focusing on planning, implementation, and evaluation. The research employed a qualitative approach with a multi-site case study design at MAN 1 Bandar Lampung and MAN 2 Bandar Lampung. Data were collected through observation, interviews, and documentation and analyzed using data condensation, data display, and conclusion drawing techniques. The findings revealed that teacher professional development planning was carried out through needs analysis, academic supervision, and Teacher Performance Assessment (PKG). The implementation was conducted through In-House Training (IHT), MGMP activities, workshops, seminars, academic supervision, and technology training. Evaluation was conducted through PKG, academic supervision, and classroom observation. Overall, the management of teacher professional development has been implemented effectively and has contributed to improving teacher competence and the quality of learning in madrasahs.